2006
DOI: 10.2353/ajpath.2006.060269
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Peptide Remnants in AN-1792-Immunized Alzheimer's Disease Patients

Abstract: Experiments with amyloid-␤ (A␤)-42-immunized transgenic mouse models of Alzheimer's disease have revealed amyloid plaque disruption and apparent cognitive function recovery. Neuropathological examination of patients vaccinated against purified A␤-42 (AN-1792) has demonstrated that senile plaque disruption occurred in immunized humans as well. Here, we examined tissue histology and quantified and biochemically characterized the remnant amyloid peptides in the gray and white matter and leptomeningeal/cortical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
196
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(209 citation statements)
references
References 74 publications
12
196
1
Order By: Relevance
“…Our results not only help to better define the mechanisms underlying immunotherapy-induced changes in amyloid, but also point to icv delivery as a superior therapeutic route for delivering anti-A␤ antibodies to the brain that can significantly reverse behavioral deficits and reduce AD-related pathological changes, and importantly, also reduce CAA and associated micro-hemorrhages. We used a mouse monoclonal IgG 1 , 6E10, that recognizes the N terminus of human A␤ and binds to the monomer, parenchymal plaques, and CAA (19,32,33). In this respect, the A␤-binding properties of 6E10 are similar to the properties of anti-A␤ antibodies generated in subjects immunized with AN1972 in the aforementioned active immunotherapy trial (14,34,35).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Our results not only help to better define the mechanisms underlying immunotherapy-induced changes in amyloid, but also point to icv delivery as a superior therapeutic route for delivering anti-A␤ antibodies to the brain that can significantly reverse behavioral deficits and reduce AD-related pathological changes, and importantly, also reduce CAA and associated micro-hemorrhages. We used a mouse monoclonal IgG 1 , 6E10, that recognizes the N terminus of human A␤ and binds to the monomer, parenchymal plaques, and CAA (19,32,33). In this respect, the A␤-binding properties of 6E10 are similar to the properties of anti-A␤ antibodies generated in subjects immunized with AN1972 in the aforementioned active immunotherapy trial (14,34,35).…”
mentioning
confidence: 96%
“…The discontinued phase II trial of active immunization with aggregated A␤ as an immunogen (AN1792) along with the QS-21 adjuvant demonstrated some clinical benefit in AD subjects who developed a robust anti-A␤ antibody response (14,15). The autopsy reports of 4 subjects from this trial who survived up to 20 months after their first immunization revealed focal clearance of parenchymal plaques in the cortex (16)(17)(18)(19). In contrast, the accumulation of amyloid in cerebral blood vessels, also known as cerebral amyloid angiopathy (CAA), was more severe than observed in non-immunized patients at a similar stage of AD, with multiple cortical hemorrhages evident in one case (17,19,20).…”
mentioning
confidence: 99%
See 3 more Smart Citations